Arah Investasi dan Prospek Perekonomian Indonesia di Tengah Perubahan Global - Harahap, Desi Khairani; Pangaribuan, Laili Rohimah; Winanda, Putri; Hasibuan, Reni Ria Armayani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes investment trends and Indonesia's economic potential in the context of dynamic global developments, marked by geopolitical conflicts, disruptive technological innovations, and energy conservation. The national methodological approach applied includes literature review and qualitative descriptive analysis based on secondary data from domestic and international institutions. The findings show that Indonesia has strong economic resilience, but faces major obstacles in attracting quality investment. Indonesia's investment orientation focuses on export-oriented manufacturing industries, further processing of natural resources, and the digital economy. The potential for Indonesia's future economic reform is highly dependent on successful structural implementation, human resource development, and energy conservation. Key recommendations include strengthening the regulatory framework that supports investment and diversifying trading partners to reduce global risks.